1976
DOI: 10.1037/0022-006x.44.3.340
|View full text |Cite
|
Sign up to set email alerts
|

Process and outcome in psychotherapy and behavior therapy.

Abstract: Three behavior therapists and three analytically oriented psychotherapists treated a total of CO neurotic outpatients for 4 months. Measures of Rogers-Truax factors, nonlcxical speech characteristics, therapist informational specificity, and a content analysis of therapist activity were taken from recordings of the fifth interview. Therapists rated their feelings toward their patients, and patients completed the Relationship Questionnaire and the Lorr Inventory. In psychotherapy, patients who were most liked b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 2 publications
2
15
0
Order By: Relevance
“…In a carefully evaluated clinical study. Staples, Sloane, Whipple, Cristol, and Yorkston (1976) found that for clinical outpatients who received various behavioral treatments, a clear trend emerged in which clients who perceived higher levels of nonpossessive warmth and accurate empathy evidenced more improvement thar. those who did r.ct.…”
Section: O 3 ^mentioning
confidence: 99%
“…In a carefully evaluated clinical study. Staples, Sloane, Whipple, Cristol, and Yorkston (1976) found that for clinical outpatients who received various behavioral treatments, a clear trend emerged in which clients who perceived higher levels of nonpossessive warmth and accurate empathy evidenced more improvement thar. those who did r.ct.…”
Section: O 3 ^mentioning
confidence: 99%
“…At the other extreme are more directive counselors such as Haley (1963) and Ellis (1972), who advocate more active control over what the client is to do in counseling. Researchers have found that, indeed, counselors who espouse less directive positions behave in ways fitting their beliefs (i.e., they exhibit fewer directive type behaviors), as do those who hold to more directive theories (Hill, Thames, & Rardin, 1979;Lee & Uhlemann, 1984;Staples, Sloane, Whipple, Cristol, & Yorkston, 1976). From these results, it has been concluded (Pope, 1977;Staples et al, 1976) that some counselors are more controlling than others because they exhibit more of these directive, controlling type behaviors.…”
mentioning
confidence: 99%
“…These different definitions were examined by studying who determined the topic of conversation. This topic control variable has been used previously in the literature as a process measure of control (Staples et al, 1976;Verplanck, 1955) and seems especially important in counseling, given that the primary activity is verbal discourse. Specifically, the proportion of topic initiations, the intrapersonal definition of control, was correlated to the proportion of topic initiations that were subsequently followed, the interpersonal definition.…”
mentioning
confidence: 99%
“…However, in a follow-up paper, Staples, Sloane, Whipple, Cristol, and Yorkston (1976) extended this earlier N of 17 to 60 patients, choosing their additional 43 patients from among those seen by behavior therapists as well as by psychotherapists. Although reporting their findings in this follow-up paper by bar graphs rather than by correlations, they found with this larger N what appear to be even stronger relationships between speech and empathy than those shown in our Table 1 from their initial study.…”
Section: -28)mentioning
confidence: 99%